MANAJEMEN KELAS DI TAMAN KANAK-KANAK AL HUSNA BOGOR - Suryani; Hasanah, Tita; Lestari, Hana (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2024)
This research aims to determine the implementation of classroom management in A-accredited kindergartens. The research method used is descriptive qualitative. The location of the research was Al Husna Kindergarten, Bogor Regency in the 2023/2024 academic year. The informants in this research were the school principal and class teacher. Data collection techniques using observation, interviews and documentation. Data analysis technique with data reduction process and drawing conclusions. Data validity testing was carried out using technical triangulation. The results of the research show that class management at Al Husna Kindergarten includes planning in the form of determining curriculum and learning, organizing educators and facilities and infrastructure, implementing according to planning with supervision by the principal and supervision by supervisors. Apart from that, findings were obtained in the form of inhibiting and supporting factors in implementing classroom management.